On the Convergence Rate of Spectral Approximations for the Equations of Nonhomogeneous Incompressible Fluids. (29th December 2020) - Ortega-Torres, E.; Poblete-Cantellano, M.; Rojas-Medar, M. A.
Abstract: In this paper, we are concerned about the convergence rates of spectral semi-Galerkin methods to solve the equations describing the motion of a nonhomogeneous viscous incompressible fluid. This approach allows the study of density dependent viscosity.